Multiple modes of cell death in neuroendocrine tumors induced by artesunate - Yan, Ge; Dawood, Mona; Böckers, Madeleine; Klauck, Sabine; Fottner, Christian; Weber, Matthias M.; Efferth, Thomas (Phytomedicine, 2020)
Background - The paucity of effective treatment in neuroendocrine tumors (NETs) encouraged us to investigate the therapeutic value of artesunate (ART) promised by its inhibitory effect against various tumors and broad safety profile. - Methods - We evaluated the impact of ART on three NET cell lines, BON-1, QGP-1 and NCI-H727 on cellular and molecular levels. - Results - Our results showed that ART induced endoplasmic reticulum (ER) stress through phosphorylation of eIF2α, which further gave rise to autophagy in all three NET cell lines. Specifically, apoptosis and ferroptosis were also observed in BON-1 cells, which made BON-1 cell line more vulnerable upon ART treatment. The different sensitivities presented on the three cell lines also associated with a differential regulation of p21 on the long run. Co-treatment with p21 inhibitor UC2288 showed an additive effect on QGP-1 and NCI-H727 cell lines indicating p21 upregulation in these two cell lines might confer resistance towards ART treatment. - Conclusions - It is possible to include ART in the treatment of NETs in the future.